A New Biorecognition-Element-Free IDμE Sensor for the Identification and Quantification of E. coli - Yung-Kai Lin; Hsing-Ju Wu; Nguyen Van Hieu; Pei-Yi Chu; Thi Vien Thao Do; Fiona Yan-Dong Yao; Thien Luan Phan; Congo Tak Shing Ching (Biosensors, 2022)
The label-free biosensor has emerged as an effective tool for the purpose of early detection of causative pathogens such as Escherichia coli as a preventive measure. In this study, a biorecognition-element-free interdigitated microelectrode (IDμE) sensor is designed and developed with this in mind, with good reliability and affordability. Results show that the designed sensor can identify E. coli with good selectivity using an impedance and capacitance of 7.69 MHz. At its optimum impedance of 1.3 kHz, the IDμE sensor can reliably quantify E. coli in a range of measurement (103.2~106 cfu/mL), linearity (R2 = 0.97), sensitivity (18.15 kΩ/log (cfu/mL)), and limit of detection (103.2 cfu/mL). In summary, the IDμE sensor developed possesses high potential for industrial and clinical applications.